Tailoring Safety Practices for AI Innovation: A Model for Nigeria’s Socioeconomic Context - Oveh, Richard O.; Aziken, G.; Atomatofa, E. (Journal of Science Research and Reviews, 2025)
Artificial Intelligence (AI) is rapidly transforming industries and societies worldwide. However, its adoption in Nigeria poses unique challenges and opportunities due to the country’s socioeconomic context. This paper explores the development of safety practices tailored to Nigeria’s distinctive characteristics. A quantitative method was used. A questionnaire was first used to understand the awareness, implementation and challenges of using Artificial Intelligence (AI) safely in a work environment. A Comparative Framework Analysis examining successful AI safety models from other regions was then conducted to extract adaptable strategies. The results suggest that while there is significant awareness and adoption of AI safety practices, there are still notable challenges, particularly in the areas of resources, training, and implementation. The high prevalence of AI-related safety incidents and the lack of confidence in organizations’ abilities to handle these risks point to gaps in the existing safety frameworks. A framework with multidisciplinary approach to AI safety in Nigeria was then proposed. It offers a promising solution by integrating technical, regulatory, and sociocultural perspectives. It is recommended that efforts should focus on improving awareness, enhancing training programs, and ensuring that AI safety guidelines are both accessible and adaptable to local contexts.